Komparasi Penokohan dari Novel ke Film Seperti Dendam Rindu Harus Dibayar Tuntas - Eriana, Anida; Ekawati, Mursia; Rizal, M. Daniel Fahmi (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
The transition of written literary works into cinematic literary works is referred to as ecranization, linguistically the process of transferring from a literary work to film form. The research entitled